En contra de los impíos. La Actuación de la Buena Prensa Católica en la Arquidiócesis de Santiago, 1906-1936 - Loyola, Manuel (Ariadna Ediciones, 2016)
Catholic project of the Good Press and its impact on Chilean society of the early twentieth century